Analisis Biaya Produksi Dalam Penganggaran UMKM Bakso Zaky Di Pancur Batu - Gracenda Febina Br Purba; Dita Marsela Saragih; Hendriadi Hasibuan; Jekky Ginting; Julius Wisesha Simanjuntak; Lokot Muda Harahap (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Bakso Zaky stall business located in Deli Serdang district, North Sumatra has been established since 2019. Mr. Zaky started his business with capital of IDR 12,500,000. The location of this business stall is very strategic because it is on the edge of the market and many people pass by it. This research method is a qualitative and secondary method, namely research that uses short-term time or with supporting data and qualitatively by conducting direct interviews with sources. The subject of this research is a meatball trader named Zaky Darius who is 31 years old. The research results obtained were that the maximum profit from chicken noodles was IDR 842,000, regular meatballs IDR 1,154,000, and large meatballs IDR 920,000, so that within a week Zaky's Bakso business experienced a net profit/profit of IDR 2,916,000.